Predictors of psychopathologic symptoms by work-related stress factors in Mental Health Professionals of a tertiary-level Psychiatric Hospital in Mexico City - María Eugenia Hernández Gutiérrez; Patricia Ortega-Andeane; Danelia Mendieta; Karla Vanessa García-Mejorado; Elvia Coballase-Urrutia; María Isabel Barrera-Villalpando; Anabel Flores Zamora; Maricela Irepan-Aguilar (Archives of Depression and Anxiety - Peertechz Publications, 2023)
Introduction: Mexico has a high prevalence of work stress; mental health professionals are a vulnerable group who experience demanding environments that place their own mental health at risk.  Objective:  The present study aimed to evaluate the work-related stress levels and development of psychopathology in mental health professionals of a tertiary-level psychiatric hospital in Mexico City.  Methods: The study included 90 mental health professionals, utilizing two questionnaires: (1) to analyze the level of occupational stress, the Stress Work Instrument (SWI) for Mexican physicians was employed; and (2) for symptomatic distress, the Symptom Checklist-90-Revised (SCL-90-R) was applied. Two theoretical assumptions' ('Effort-Reward' for Karasek and "Effort-Reward Imbalance" for Siegrist) were used to propose an analytical model based on structural equations.  Results: The model obtained showed a high and positive structural coefficient (0.76). The goodness-of-fit for the model was acceptable (χ2 = 51.22, p = .02; CFI = .97; RMSEA = 0.08). This study showed a causal explanation for the generation of distress, and the model detected a strong and significant effect from work stress to distress.  Conclusion: We conclude that the model obtained predicts a significant effect of work-related stress on mental health such as anxiety, depression, somatization, and feelings of inadequacy in mental health professionals. Therefore, work-related stress factors should be minimized thus preventing distress to ensure that psychiatric personnel enjoy physical and mental health enabling them for efficient and professional clinical practice.